U.S. network and low-cost carriers' performance in response to COVID-19: Strictness of government policies and passengers' panic. (January 2023) - Kaffash, Sepideh; Khezrimotlagh, Dariush
Abstract: Coronavirus outbreak has been highly disruptive for aviation sector. There is strong correlation between COVID-19 related news, volatility in transportation, low confidence in travel safety, and uncertainty in this era. In this research, we study and distinguish the COVID-19's impact on U.S. airlines' performance. The network and low-cost carriers responded differently to it in terms of capacity reduction, market share reduction, scheduled flights reduction, flight cancellations, and service quality in the year 2020. We illustrate low-cost carrier had higher efficiency compared to network ones during pandemic by applying Network Data Envelopment Analysis. Furthermore, the effects of two key factors that emerge from COVID-19, the government's stringency actions and passengers' panic, on U.S. airlines efficiency are studied. Our analysis demonstrate that the negative effect is more significant for passengers' panic than it is for governments' stringency measures. In addition, we show that passengers' panic has more impact on the efficiency of network carriers compared to low-cost carrier. Highlights: U.S. low-cost carriers have a higher efficiency than network carriers in pandemic. U.S. network carriers respond more aggressively to COVID-19 in terms of flight cancellations, reduction in scheduled flights. Network carriers recover more moderately than low-cost ones. The efficiency of U.S. carriers is more significantly affected by passengers' panic than by governments' stringency measures.